The Place of Foundations and Endowments in German History: A Historical-Statistical Approach. (April 2015) - Adam, Thomas; Lingelbach, Gabriele
This essay provides the very first account of the historical size and scope of German philanthropy from the mid-19th century to the 1950s. Our historical-statistical analysis of various unpublished and published sources about associations, foundations, and endowments supports an interpretation that suggest that foundations and endowments were important sources of financing for many public institutions in Germany. Our article dispels, thus, commonly held notions about the marginal position of philanthropy in German society and further suggests that philanthropy should be acknowledged as an important source for organizing and structuring modern German society.